EXPLORING THE POTENTIAL OF HYPERLOCAL MEDIA: BENEFITS, CHALLENGES, AND FUTURE DIRECTIONS - Jati, Rocky Prasetyo (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
Hyperlocal media is an increasingly important player in the media landscape, providing communities with targeted and relevant information. This conceptual paper aimed to explore the potential of hyperlocal media as a solution for community media in the digital era. The study analyzed the benefits of hyperlocal media for communities and discussed the key challenges and opportunities facing these media outlets. The analysis revealed that hyperlocal media could foster civic engagement, cultural preservation, public discourse, and community connection. However, the study also emphasized the need to address the sustainability of these media outlets and the importance of exploring innovative technologies and strategies to support their growth and development. This study sheds light on the significance of hyperlocal media in creating more substantial, more connected communities and highlights the need for further research in this area.